Full Reserve System and Islamic Banking System Proposal: A Comparative Study of Fractional Reserve Free-Banking Theory - Fathurrahman, Ayif; Nahar, Faiza Husnayeni (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
This article aims to compare the fractional reserve free-banking theory. The emergence of these theories is due to the impact of fractional reserve banking on the crisis and bubble economies. So that in seeing this phenomenon, the thoughts of Positive Money and the New Economics Foundation, Narrow Banking, LPB (Limited Purpose Banking), and the Chicago Plan together contribute controversial ideas to the banking monetary system, namely in the form of fractional reserve free-banking. According to some of these thoughts, the current source of modern economic instability lies in the fractional reserve banking system that is applied in commercial banking throughout the world through money creation capabilities, so that the money supply shifts from its equilibrium point. The implications of the intermediary function make Islamic banks also face the risk of 'too big to fail', considering the pattern of Islamic banks is still intermediary. This means that liquidity risks and bank runs are very likely to occur. This is reinforced by the more varied products of Islamic banks compared to conventional banks, so there needs to be an effort so that Islamic banks transform themselves from fractional reserve banking to fractional reserve free-banking with the A-F model.